Facile synthesis and characterization of V2O5 nanobelt bundles containing plasmonic Ag for photoelectrochemical water splitting under visible light irradiation. Issue 17 (1st December 2019) - Reddy, I.Neelakanta; Sreedhar, Adem; Reddy, Ch Venkata; Cho, Migyung; Kim, Dongseob; Shim, Jaesool
Abstract: V2 O5 nanobelt bundle (NBB) photoanodes were synthesized from commercial V2 O5 powder via a facile, room-temperature aqueous solution technique. The V2 O5 NBBs were several micrometers long and 15–25 nm wide, with an orthorhombic V2 O5 structure, a crystallite size of 63 nm, and an optical bandgap of 2.19 eV. The V2 O5 NBBs containing plasmonic Ag showed significantly lower charge transfer resistance than the pure V2 O5 NBBs. The charge transfer resistance was further reduced to 21.02 Ω by adding 10% methanol to the 0.1 M KOH electrolyte as a hole scavenger. The water-splitting activity of the V2 O5 and V2 O5 /Ag photoanodes was tested in 0.1 M KOH; a very low photocurrent density of 0.5 μA/cm 2 was observed under visible light illumination. The low photocurrent was ascribed to a build-up of photogenerated holes at the photoelectrode/aqueous electrolyte. The addition of methanol drastically increased the photocurrent of the V2 O5 NBB photoelectrode. A maximum photocurrent density of 0.2 mA/cm 2 was achieved for up to 230 s under light illumination for the V2 O5 NBBs containing plasmonic Ag in KOH and methanol, which was 400 times higher than that of the photoanode without a hole scavenger.